Failure to detect ward hypoxaemia and hypotension: contributions of insufficient assessment frequency and patient arousal during nursing assessments. (November 2021) - Saab, Remie; Wu, Bernie P.; Rivas, Eva; Chiu, Andrew; Lozovoskiy, Sofia; Ma, Chao; Yang, Dongsheng; Turan, Alparslan; Sessler, Daniel I.
Abstract: Background: Postoperative hypotension and hypoxaemia are common and often unrecognised. With intermittent nursing vital signs, hypotensive or hypoxaemic episodes might be missed because they occur between scheduled measurements, or because the process of taking vital signs arouses patients and temporarily improves arterial blood pressure and ventilation. We therefore estimated the fraction of desaturation and hypotension episodes that did not overlap nursing assessments and would therefore usually be missed. We also evaluated the effect of taking vital signs on blood pressure and oxygen saturation. Methods: We estimated the fraction of desaturated episodes (arterial oxygen saturation <90% for at least 90% of the time within 30 continuous minutes) and hypotensive episodes (MAP <70 mm Hg for 15 continuous minutes) that did not overlap nursing assessments in patients recovering from noncardiac surgery. We also evaluated changes over time before and after nursing visits. Results: Among 782 patients, we identified 878 hypotensive episodes and 2893 desaturation episodes, of which 79% of the hypotensive episodes and 82% of the desaturation episodes did not occur within 10 min of a nursing assessment and would therefore usually be missed. Mean BP and oxygen saturation did not improve by clinically meaningful amounts during nursing vital sign assessments. Conclusions: Hypotensive and desaturation episodes are mostly missed because vital sign assessments on surgical wards are sparse, rather than being falsely negative because the assessment process itself increases blood pressure and oxygen saturation. Continuous vital sign monitoring will detect more disturbances, potentially giving clinicians time to intervene before critical events occur.